2018
DOI: 10.15406/mojap.2018.05.00186
|View full text |Cite
|
Sign up to set email alerts
|

Aging of thymus gland and immune system

Abstract: Aging is an inevitable, progressive and irreversible process that is manifested with multiple organ dysfunction. Reactive oxygen species (ROS) is considered the main etiological factor of aging. The thymus gland is the primary site of T cell production and it represents a key organ of the immune system. It is endodermal in origin and lies in the anterior mediastinum behind the sternum. Thymic involution with aging results in less efficient T-cell development and decreased emigration of naïve T cells to the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The COVID-19 disease severity significantly increased with old age and was milder in younger age which was in concordance with several other studies [37][38][39]. This can be explained by poor health outcomes and the physiologic changes of aging which begin early in life with the drop in production of new T cells due to thymus gland involution, followed by deterioration of the immune system and increased susceptibility to infection [40]. Seventy to eighty percent of the circulating lymphocytes are composed of T lymphocytes [41].…”
Section: Discussionsupporting
confidence: 90%
“…The COVID-19 disease severity significantly increased with old age and was milder in younger age which was in concordance with several other studies [37][38][39]. This can be explained by poor health outcomes and the physiologic changes of aging which begin early in life with the drop in production of new T cells due to thymus gland involution, followed by deterioration of the immune system and increased susceptibility to infection [40]. Seventy to eighty percent of the circulating lymphocytes are composed of T lymphocytes [41].…”
Section: Discussionsupporting
confidence: 90%
“…17 The thymus gland is the primary lymphoid organ that provide site of T cell production and activation, it represents a key organ of the immune system. 18 The thymus extracts contain amino acids, this acids composition revealed a high content of acidic amino acids and no apparent homology to previously defined growth factors and thymus differentiation hormones. 19 The thymus extracts have been shown to modulate the development, maturation and activation of T cells, stimulate production of interleukin-2 (IL-2), their effect on the specialization and migration of T-lymphocytes throughout the body.…”
Section: Introductionmentioning
confidence: 91%
“…The thymus gland is the primary lymphoid organ that provide site of T cell production and activation, it represents a key organ of the immune system, (Haroun, 2018).With aging and after puberty, the thymus begins to shrink and involute and the production as well as development of T-cells reduce to a lower rate (Haroun, 2018 andJaneway et al, 2001), therefore, the thymus extracts have been shown to modulate the development, maturation and activation of T cells, stimulate production of interleukin-2 (IL-2), their effect on the specialization and migration of T-lymphocytes throughout the body. The thymus also releases hormones that regulate immune function (Colic et al, 2008).…”
mentioning
confidence: 99%
“…Schulz et al, 2015 andHaroun, 2018). The imbalance between oxidants like free oxygen radicals (reactive oxygen species, ROS) and antioxidants are considered as an important etiology of aging,(Desai et al, 2010)…”
mentioning
confidence: 99%